Marine algae from the Canary Islands especially from Teneriffe and Gran Canaria. - Boergesen, F.
Contents: I. Chlorophyceae II. Phaeophyceae III. Rhodophyceae Part 1- Bangiales and Nemalionales Part II - Cryptonemiales, Gigartinales and Rhodymeniales Part III - Ceramiales IV. Cyanophyceae